2023
DOI: 10.1186/s12871-023-01994-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of opioid-free general anesthesia for gynecological laparoscopic surgery under ERAS protocol: a non-inferiority randomized controlled trial

Abstract: Background Enhanced recovery after surgery (ERAS) is now widely used in various surgical fields including gynecological laparoscopic surgery, but the advantages of opioid-free anesthesia (OFA) in gynecological laparoscopic surgery under ERAS protocol are inexact. Aims This study aims to assess the effectiveness and feasibility of OFA technique versus traditional opioid-based anesthesia (OA) technique in gynecological laparoscopic surgery under ERAS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
(32 reference statements)
2
7
0
1
Order By: Relevance
“…We planned to observe 50 patients in the OFA group and 50 patients in the OBA group. The number of cases was determined to allow for examining a larger patient collective than had previously been done in smaller randomized studies [2][3][4][5][6]. Normal distribution for continuous data was tested using the Kolmogorov-Smirnov test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We planned to observe 50 patients in the OFA group and 50 patients in the OBA group. The number of cases was determined to allow for examining a larger patient collective than had previously been done in smaller randomized studies [2][3][4][5][6]. Normal distribution for continuous data was tested using the Kolmogorov-Smirnov test.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that 9 (18%) patients in the OBA cohort did not require piritramide. Postoperative opioid consumption (Piritramide) was lower in the OFA group (OFA: 0 [0-3.4], OBA: 6 [3][4][5][6][7][8][9]; P ≤ 0,001). 26 (52%) of 50 patients in the OFA group and 38 (77.6%) of 49 patients in the OBA group received droperidol in the PACU (chi-square test, P = 0.008).…”
Section: Secondary Outcomesmentioning
confidence: 98%
See 1 more Smart Citation
“…As research efforts continue to focus on how best to treat patients’ perioperative pain, including those with OUD, the concept of “opiate free anesthesia” (OFA) is emerging as a method to decrease the use of opioids [ 29 ]. By using a multimodal nonopioid approach to anesthesia and perioperative analgesia, patients are able to avoid opioids altogether with either similar or improved outcomes compared to standard opioid analgesia [ 30 32 ]. A meta-analysis by D’Amico and colleagues examined the use of OFA in thoracic surgery and concluded that it was associated with lower rates of complications, lower pain scales and lower morphine consumption postoperatively [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The studies were conducted in eight different countries, including one in Turkey, one in Belgium, three in Egypt, two in China, one in Germany, one in South Korea, one in Macedonia, one in Vietnam, and one in Cameroon. All studies were performed on patients undergoing laparoscopic surgery; ve studies were on gynecologic laparoscopic surgery [25][26][27][28][29], three studies were on laparoscopic cholecystectomy [30][31][32], three studies were on laparoscopic bariatric surgery [33][34][35], and one study was on laparoscopic radical colon surgery [36]. All studies were randomized controlled trials and the intervention studied was OFA, a detailed description of the anesthetic drugs used is given in Table 1.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%